THE INFLUENCE OF PROFITABILITY TO THE COMPANY VALUE WITH CORPORATE SOCIAL RESPONSIBILITY AS A VARIABLE MODERATION Case Studies on Companies Listed in the Sri Kehati Index for the 2012-2016 Period - Eddy Winarso; Veronica Christina M.P. (Journal of International Conference Proceedings (JICP), 2019)
This study aims to determine whether the company value as measured by price book value is influenced by the company's ability to obtain profits measured by Return on Assets and moderated by corporate social responsibility in companies listed on the SRI - KEHATI index for the period 2012 - 2016. Researchers are interested in conducting research This is because Investors in determining stock investment see the ability to obtain corporate profits but also see whether the company has carried out social responsibility for nature and the social environment around the company or called green investment. The company has carried out corporate social responsibility which can be seen from whether the company has carried out CSR in accordance with the GRI index set by the government with 79 indicators. In this study using corporate social resposibility as a moderating variable with a number of samples of annual report research of 18 companies listed on the SRI - KEHATI Index from 2012 - 2016 and found that profitability as an independent variable and corporate social responsibility as a moderating variable has a positive effect on value The company measured by Price book value is 72.40% meaning that profitability and corporate social responsibility have a strong match in assessing the company's performance, while 27.60% is influenced by other variables not examined.